2005
DOI: 10.3349/ymj.2005.46.6.799
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Trans-Arterial Injection of166Holmium-Chitosan Complex for Treatment of Small Hepatocellular Carcinoma

Abstract: Percutaneous approaches, such as percutaneous ethanol injection and radiofrequency ablation, have been most widely used for hepatocellular carcinoma patients who were not eligible for surgery. New technologies to improve the efficacy are currently needed. 166Holmium is a neutron activated radionuclide, and has several beneficial radiophysical characteristics for internal radiation therapy. 166Holmium-Chitosan complex, in which chitosan is chelated with 166Holmium, was developed as a radiopharmaceutical for can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…166 Ho has seen a wide range of applications in cancer therapy over the last few decades (Shi et al 2017 ). A wide array of therapeutic applications have been investigated with pre-clinical and clinical trials and studies being reported for radiopharmaceutical therapies for bone marrow cancer (Bayouth et al 1995a , b ; Giralt et al 2003 ; Christoforidou et al 2017 ), metastatic bone pain palliation (Voorde et al 2019 ; Bahrami-Samani et al 2010 ), brain cancer (Huh et al 2005 ; Ha et al 2013 ), liver cancer (Cho et al 2005 ; Kim et al 2006 ), and prostate cancer (Seong et al 2005 ; Kwak et al 2005 ), among others. This radionuclide has gained attention for its potential theranostic applications due to its favourable decay characteristics that allow for its use as both a therapeutic agent and an imaging agent (Tan et al 2020 ).…”
Section: Holmium: 166 Homentioning
confidence: 99%
“…166 Ho has seen a wide range of applications in cancer therapy over the last few decades (Shi et al 2017 ). A wide array of therapeutic applications have been investigated with pre-clinical and clinical trials and studies being reported for radiopharmaceutical therapies for bone marrow cancer (Bayouth et al 1995a , b ; Giralt et al 2003 ; Christoforidou et al 2017 ), metastatic bone pain palliation (Voorde et al 2019 ; Bahrami-Samani et al 2010 ), brain cancer (Huh et al 2005 ; Ha et al 2013 ), liver cancer (Cho et al 2005 ; Kim et al 2006 ), and prostate cancer (Seong et al 2005 ; Kwak et al 2005 ), among others. This radionuclide has gained attention for its potential theranostic applications due to its favourable decay characteristics that allow for its use as both a therapeutic agent and an imaging agent (Tan et al 2020 ).…”
Section: Holmium: 166 Homentioning
confidence: 99%
“…[16][17] Following these results, 166 Ho-chitosan (DW-166HC) has been approved in Korea as a radiopharmaceutical for the treatment of small hepatocellular carcinoma (HCC). 18,19 However, DW-166HC is sensitive to degradation induced by radiation and its use immediately after synthesis is highly required.…”
Section: Introductionmentioning
confidence: 99%